2011
DOI: 10.1074/jbc.m111.253898
|View full text |Cite
|
Sign up to set email alerts
|

Unique Structural and Nucleotide Exchange Features of the Rho1 GTPase of Entamoeba histolytica

Abstract: Background: Rho family GTPases regulate Entamoeba histolytica pathogenesis. Results: Despite Ras-like structural features and fast intrinsic nucleotide exchange, EhRho1 engages classical Rho effectors and regulates actin. Conclusion: EhRho1 is a true Rho family GTPase with a unique mode of nucleotide interaction. Significance: Possibly representing an early Rho subfamily divergence from the Ras superfamily, EhRho1 likely regulates actin polymerization in E. histolytica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
59
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 54 publications
5
59
0
2
Order By: Relevance
“…In previous work (7), we demonstrated that EhRho1 binds the GBD-FH3 domain tandem of EhFormin1 (a.a. 69-445) selectively in its GTPγS-bound, activated conformation. Since some minor degradation of that particular GBD-FH3 fragment was reported during expression and purification ( e.g.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…In previous work (7), we demonstrated that EhRho1 binds the GBD-FH3 domain tandem of EhFormin1 (a.a. 69-445) selectively in its GTPγS-bound, activated conformation. Since some minor degradation of that particular GBD-FH3 fragment was reported during expression and purification ( e.g.…”
Section: Resultsmentioning
confidence: 80%
“…A recent proteomic characterization of E. histolytica cysts indicated that EhFormin1 is expressed during both the encysted and trophozoite life cycle stages (22). We recently showed (7) that the GBD-FH3 domain tandem of EhFormin1 binds EhRho1 in a nucleotide state-dependent fashion, which is typical of Rho GTPase/effector interactions. Furthermore, expression of constitutively active EhRho1 in fibroblasts induced stress fiber formation (7), suggesting that EhRho1 might regulate actin filament formation in E. histolytica trophozoites through EhFormin1 or other effectors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Open reading frames of Ehubiquitin (AmoebaDB accession EHI_083410), Ehuba1 (EHI_020270), Ehubc5 (EHI_083560), Ehring1 (EHI_020100), Ehhect1 (EHI_011530), and Ehhect2 (EHI_124600) were PCR amplified from genomic DNA and subcloned as hexahistidine fusions into a pET vector-based ligation-independent cloning vector, pLIC-His, as described previously (19). PCR primer sequences were: Ehubiquitin, 5Ј-ATGCAAATATTTGTTAA-GAC-3Ј and 5Ј-TTAATATCCTCCTCTTAATC-3Ј; Ehuba1, 5Ј-ATGACACAACAAATTGATGAAGCCGTATTG-3Ј and 5Ј-TTAGAAATTCAAAAGAACATCTGGAAATTC-3Ј; Ehubc5, 5Ј-ATGGCTATGCGTAGAATTCAAAAAG-3Ј and 5Ј-TTAT-GGTCGAGCATACATAC-3Ј; Ehring1, 5Ј-ATGTCAAGAGA-AGATTGTG-3Ј and 5Ј-TTAGTGATAAATAATTCGGTG-3Ј; Ehhect1, 5Ј-ATGCGGAAACACCTCAAATAACAAATAA-3Ј and 5Ј-TTAAATTAAACCAAATCCATTTGTATT-3Ј; Ehhect2, 5Ј-ATGAGACCGGCTTGGAGACTTA-3Ј and 5Ј-TTAAGA-AAATGCAAATCCTGATTTTGATG-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Surface Plasmon Resonance (SPR) Assays-SPR-based measurements of protein-protein interactions were performed on a Biacore 3000 (GE Healthcare), essentially as described previously (19). Briefly, purified His 6 -EhUbc5 and His 6 -EhUbc5(F62A) proteins were separately immobilized on an NTA biosensor chip using covalent capture coupling (27).…”
Section: Methodsmentioning
confidence: 99%